Expressão de Her-2 em tumores mamários de gatas - Gundim, Lígia Fernandes (2017)
Mammary neoplasms are the third most frequent type of neoplasm in felines and the search for prognostic factors for this type of tumor in cats has intensified in recent years, given its high frequency and relevance in feline clinics. Among the immunohistochemical markers used for prognosis, the Human Epidermal Growth Factor Receptor type 2 (Her-2) receptor, which in women is associated with a worse prognosis, stands out. The objective of this study was to evaluate the expression of Her-2 in hyperplasias and benign and malignant neoplasms of cats and to relate the expression to the type and histological grade of mammary carcinomas. Thirty-eight cases of neoplasia and mammary hyperplasia of cats were selected from 2006 to 2016. From the protocols selected, epidemiological information and macroscopic characteristics of mammary lesions were obtained. Tumors were individually classified and graded histologically by two pathologists. Her-2 expression was determined by immunohistochemistry, using a semi-quantitative analysis of the slides according to the Hercepest (Dako) recommended score. The Chi-square test (χ2) was used to evaluate the relationship between Her-2 expression and type of mammary lesion, histological types of carcinoma and histological grade (P <0.05). The mean age of the animals was 8.5 years and young cats were affected only by benign hyperplasias and neoplasms. Undefined cats were more affected (84.37%), followed by Siamese (9.37%) and Persian (6.25%). Regarding the histological classification, 18.42% of the mammary lesions were classified as hyperplasia, 18.42% as adenoma and 63.16% were classified as carcinoma. The most common type of carcinoma was tubulopapillary carcinoma (66.7%), followed by solid carcinoma (25%) and cribriform carcinoma (8.33%). Her-2 overexpression was observed in 4 samples (16.7%) of tubulopapillary carcinoma, two carcinomas grade I and two degrees II, but there was no relationship between Her-2 expression and type of mammary lesion (P = 0.3127), carcinoma type (0.3446) or histological grade (0.6485). It is concluded that the percentage of female mammary carcinomas expressing Her-2 is lower than in women's breast cancer and there was no relation between grade and histological type and Her- 2 expression.